Sensores eletroquímicos e dispositivo analítico combinado a smartphone fabricados por impressão 3D para o controle de qualidade de combustíveis - João, Afonso Filipe (2021)
The analytical development of sensitive and accessible methods, feasible in places without high technology, which provide equivalent results to those obtained using conven-tional methods of analysis is the fundamental purpose of carrying out this work. Firstly, a smartphone was used with the previously installed color grab application that had an RGB color model interface, to read samples of fuel ethanol in determination of iron (III). For this purpose, an auxiliary camera “dark chamber” was built using 3D printing in Styrene-butadiene-acrylonitrile (ABS), to guarantee constant lighting when acquiring the image pro-vided by the cell phone flash. The correlation between the concentration of Fe (III) and the color intensity was obtained after the transformation of the RGB components into a gray scale model (grayscale model). Its results were compared to those obtained by spectrophotometry and the results had no statistically significant differences, with a linear response of 0.5 and 10 mg L-1 (R2 = 0.998) and limit of detection 0.1 mg L-1. Then, electrochemical electrodes were developed using a 3D printer (planar working electrode) and using a 3D pen (cylindrical working electrode), both manufactured with polymeric filament containing carbon black and polylactic acid (CB / PLA). After the CB / PLA electrodes were subjected to the electrochemical surface treatment, which gave a great increase in the response of the analytes, the electrodes were used to determine metals in fuel ethanol, after simple dilution of the samples in support electrolyte (0.1 mol L-1 HCl). Finally, an electrochemical sensor was manufactured using a 3D pen (cylindrical electrode) and filaments of graphene and polylactic acid (G / PLA) for moni-toring the antioxidant tert-butylhydroquinone (TBHQ) in biodiesel and biokerosene. The elec-trochemical treatment of the printed electrode surface facilitated the electrochemical oxidation of TBHQ in Britton – Robinson buffer electrolyte (BR) 0.12 mol L − 1 (pH = 4.05) with the sodium dodecyl sulfate surfactant to form the emulsion with biodiesel or biokerosene. The proposed voltammetric sensor had a wide linear range (0.3 - 400 μmol L − 1, r > 0.99). The limit of detection (LOD) was estimated at 0.1 μmol L − 1 and the limit of quantification (LOQ) was 0.3 μmol L−1. The Fe3+, Pb2+, Cu2+, Mn2+ and Cr2+ cations did not interfere with the TBHQ signal in biodiesel or biokerosene. All electrodes manufactured by 3D printing (3D printer or pen) showed high precision (Inter-electrode, n = 3, DPR <5%). All analytical meth-ods proposed in this thesis with the aid of 3D printing are portable and can be applied in field for the quality control of fuels.